2016
DOI: 10.14710/tataloka.18.2.67-75
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Tata Ruang Wilayah Terhadap Aktivitas Kewirausahaan Dan Pertumbuhan Usaha Peternakan Ayam Broiler Di Provinsi Jambi

Abstract: <div><p class="AbstractEnglish">Spatial is one issue that is important in assessing the concept of entrepreneurship. Interest studied the problems of spatial and entrepreneurship is to create business growth, through the support of business locations atmosphere, leading to the creation of entrepreneurial activity. The purpose of this study to (1) identify the determining factors of the characteristics of the zone; (2) to analyze the influence of the characteristics of the zone of entrepreneurial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Changes in the use of production input types by pepper farmers indicate that the form of innovation carried out by farmers occurs in the application of new methods of production. The results of research Astuti et al, (2016) found that innovation is a characteristic of farmers who form the entrepreneurial activities of broiler breeders. The adoption of new methods of production is done by breeders as a form of innovation by doing better things.…”
Section: Entrepreneurial Characteristics Of Muntok White Pepper Famentioning
confidence: 99%
“…Changes in the use of production input types by pepper farmers indicate that the form of innovation carried out by farmers occurs in the application of new methods of production. The results of research Astuti et al, (2016) found that innovation is a characteristic of farmers who form the entrepreneurial activities of broiler breeders. The adoption of new methods of production is done by breeders as a form of innovation by doing better things.…”
Section: Entrepreneurial Characteristics Of Muntok White Pepper Famentioning
confidence: 99%